Consistency of Recall for Deployment-Related Traumatic Brain Injury. Issue 5 (September 2016) - Alosco, Michael L.; Aslan, Mihaela; Du, Mengtian; Ko, John; Grande, Laura; Proctor, Susan P.; Concato, John; Vasterling, Jennifer J.
Abstract : Objective: To examine the temporal consistency of self-reported deployment-related traumatic brain injury (TBI) and its association with posttraumatic stress disorder (PTSD) symptom severity. Setting: In-person interviews at US Army installations (postdeployment); phone interviews (long-term follow-up). Participants: A total of 378 US Army soldiers and veterans deployed to Iraq; 14.3% ( n = 54) reported TBI with loss of consciousness during an index deployment. Design: Participants were evaluated after returning from deployment and again 5 to 9 years later. Main Measures: Temporal consistency of TBI endorsement based on TBI screening interviews; PTSD Checklist, Civilian Version. Results: The concordance of deployment-related TBI endorsement from the postdeployment to long-term follow-up assessment was moderate (κ = 0.53). Of the 54 participants reporting (predominantly mild) TBI occurring during an index deployment, 32 endorsed TBI inconsistently over time. More severe PTSD symptoms at postdeployment assessment were independently associated with discordant reporting ( P = .0004); each 10-point increase in PCL scores increasing odds of discordance by 69% (odds ratio = 1.69; 95% confidence interval, 1.26-2.26). Conclusions: Deployment-related TBI may not be reported reliably over time, particularly among war-zone veterans with greater PTSD symptoms. Results of screening evaluations for TBI history should be viewed with caution in the context of PTSD symptom history.